KAFA'AH IN MARRIAGE FROM THE PERSPECTIVE OF MAQASID AL-SYARI'AH (Case Study on Darul Ma'sum Islamic Boarding School and Darussalam Foundation, Probolinggo Regency) - Muhamad Agus Salim; Fauziyah Putri Meilinda (Universitas Nurul Jadid, 2025)
This study examines the concept of kafa’ah (marital compatibility) from the perspective of Maqashid al-Shariah, using a case study of Darul Ma’sum Islamic Boarding School and Darussalam Foundation in Probolinggo Regency. The research is motivated by social phenomena within Islamic boarding schools (pesantren), where the application of kafa’ah varies between a traditional approach emphasizing equality in lineage, social status, and religious scholarship and a more contextual interpretation that prioritizes welfare (maslahah), happiness, and spiritual responsibility. The aim of this research is to analyze how the principles of Maqashid al-Shariah are applied in understanding and interpreting kafa’ah within pesantren culture, and how religious and social values interact in marital practices. The study employs a qualitative method with a phenomenological approach, utilizing in-depth interviews and document analysis. This approach enables the researcher to explore the subjective experiences of pesantren leaders in determining marital suitability based on both religious and social considerations. The findings reveal that Darul Ma’sum tends to apply kafa’ah normatively to preserve hifz al-din (protection of religion) and hifz al-nasl (protection of lineage), whereas Darussalam emphasizes hifz al-nafs (protection of life) and individual welfare. Through the analytical lens of Maqashid al-Shariah, the study concludes that a contextual and humanistic understanding of kafa’ah aligns more closely with the higher objectives of Islamic law, which seek to ensure happiness, justice, and harmony within the family. This research recommends reinterpreting kafa’ah beyond social hierarchy toward spiritual, moral, and emotional equilibrium as the foundation of a harmonious marriage.